A new approach to the evaluation of ejection friction in micro injection molding. (February 2021) - Masato, Davide; Sorgato, Marco; Lucchetta, Giovanni
Abstract: The ejection phase influences the quality and integrity of micro injection molded parts. The successful design of robust micro mold ejection systems requires studying the tribological interactions at the mold/polymer interface. At the micro-scale, the tooling topography can have a significant impact on the ejection friction. Here we propose a novel approach to the evaluation of ejection friction in micro injection molding. The two main contributors to the ejection force are the normal force due to shrinkage and the static friction coefficient. The former is addressed by developing a procedure for shrinkage characterization at the micro-scale. The latter is studied using experimental measurements of the ejection force in micro injection molding. Comparing the numerical and the experimental results allows identifying the friction coefficient as a function of polymer, process parameters, and mold surface roughness.